IQTISODIY MODERNIZATSIYASI VA GLOBAL MEGATRENDLAR SINERGIYASI (Marketing Journal, 2026)
AbstractThis article examines global megatrends and their impact on Uzbekistanʼseconomic policy. In particular, such areas as digital transformation, green economy,urbanization, and changes in the labor market are analyzed. The article analyzes theextent to which strategic documents and reforms adopted by the government ofUzbekistan are in line with global trends and considers opportunities for adaptation.The research results demonstrate the relevance of a megatrend-based approach inensuring the long-term economic stability of the republic.Keywords: Megatrends, economic policy, digital transformation, green economy,urbanization, sustainable development, strategic planning.